The writing engagement scale: a formative assessment tool - Samantha T. Ives.; R. Stacy Fields; Bonnie Barksdale; Jonathan Marine; Paul Rogers (New Jersey: Wiley Company, 2023)
This article shares a valid and reliable tool to assess student writing engagement. The Writing Engagement Scale- the WES- informs writing instruction to enhance performance.
Keywords: Writing